Yolk–shell N-doped carbon coated FeS2 nanocages as a high-performance anode for sodium-ion batteries. Issue 23 (28th May 2019) - Zang, Rui; Li, Pengxin; Guo, Xin; Man, Zengming; Zhang, Songtao; Wang, Chengyin; Wang, Guoxiu
Abstract : Rationally designed yolk–shell structured N-doped carbon coated FeS2 nanocages demonstrate superior high-rate and long-term cycling performance as anode materials for sodium-ion batteries. Abstract : Pyrite FeS2 displays brilliant prospects for sodium storage because of its high theoretical capacity (894 mA h g −1 ), low cost and eco-friendly properties. The practical application of FeS2, however, has been thwarted by poor cycle life derived from the large volume change and active sulfide loss upon sodiation/desodiation. Herein, we fabricated yolk–shell nitrogen-doped carbon-coated FeS2 nanocages (PFS@NC) by a facile thermal-sulfurization of polypyrrole-coated Prussian blue precursors for sodium-ion batteries. The yolk–shell structure affords enough space to buffer the volumetric change of FeS2 nanoparticles during the sodiation process. Therefore, the structural integrity of PFS@NC can be preserved without deforming the carbon shell. Additionally, the nitrogen-doped carbon not only improves the electronic conductivity of the composite, but also effectively traps the soluble reduced products of FeS2, contributing to its stable cycling performance. As a result, a high specific capacity of 375 mA h g −1 has been achieved up to 1000 cycles at 5 A g −1 (92% capacity retention). The PFS@NC composite could be an excellent anode material for sodium storage and the as-developed synthetic strategy is expected to be utilized for improving the performance of other metal sulfide electrode materials.